(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
The current study set out to probe the relationship between Willingness to Communicate (WTC) and different components of Early Maladaptive Schemas (EMSs). Moreover, the study sought to discover whether any subcomponents of the EMSs significantly predicts the WTC of Iranian EFL learners. One hundred fifty intermediate EFL learners took a Nelson test, and 109 learners with scores within the range of ± one standard deviation from the mean were selected. The selected learners filled out two questionnaires measuring WTC and EMSs. The results of statistical analyses indicated that there was a statistically negative and significant relationship between WTC and the seclusion and defect/shyness components of EMSs. Moreover, it was revealed that none of the components of EMSs could significantly predict WTC. Based on the findings, the seclusion and defect/shame components of EMSs should be the focus of more attention if the target is to raise learners’ WTC.